Combining Ability of Female Channel Catfish, Ictalurus punctatus, and Male Blue Catfish, I. furcatus, for Early Growth Performance of Their Progeny - Ramjie Odin; Ahmed Elaswad; Karim Khalil; Khoi Vo; Nathan J. C. Backenstose; Zachary Taylor; David Drescher; William S. Bugg; Dalton Robinson; Kamal Gosh; Zhi Ye; Guyu Qin; et al. (Fishes, 2024)
The hybrid between the female channel catfish (Ictalurus punctatus) and the male blue catfish (I. furcatus) is the best genetic type currently available for commercial catfish farming due to their superior traits. However, further genetic improvements can be achieved by selecting parents with increased combining abilities. Twenty female channel catfish and twelve male blue catfish were crossed in a partial factorial mating design, resulting in forty hybrid families. These families were evaluated for early growth in three different rearing systems, including ponds and aquaria. The early growth performance of hybrid catfish was significantly (p < 0.05) affected by the additive gene action of the female parent and the male parent. There were genotype–environment or genotype–age interactions affecting the combining abilities, both the amount and the type of genetic variation. Dam GCA was significant in all environments/ages; however, sire GCA was variable, and SCA was not significant. These findings suggest that reciprocal recurrent selection for growth could potentially improve the performance of F1 hybrid catfish.